Comparative analysis of n-hexane and ethyl acetate extracts of Arisaema propinquum via Fourier Transform Infrared Spectroscopy (FTIR) (International Journal of Food and Nutritional Sciences, 2022)
The present study is the first time investigation of major functional groups via Fourier transform infrared spectrometer (FTIR) in n-hexane and Ethyl acetate leaf/stem extracts of an unexplored medicinal herb Arisaema propinquum of North-western Kashmir Himalayas. In ethyl acetate extract, the major absorption peaks were 3377 cm-1(corresponding to O-H stretching),2918 cm-1 and 2847 (corresponding to C-H stretching in alkane),1703 cm-1(corresponding to C=O stretching), thus reflecting presence of polyphenols.Similarly, in the n-hexane extracts, the prominent absorption peaks were 3649 cm-1(corresponding to N-H stretching),3116 cm-1(corresponding to C-H stretching in alkene),2914 cm-1,2847 cm-1(corresponding to C-H stretching in alkane), reflecting presence of non-polar compounds like terpenoids and flavonoids. Dietary polyphenols and flavonoids are potent free radical suppressor’s important life saving molecules against cardiovascular diseases, ageing, anti inflammatory signalling pathways and are thus leading in pharmacology and cosmetic industries.